Annual leave entitlement policy and deduction of wages - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis, 2009)
INTRODUCTION: Annual leave, which is also commonly known as 'recreation leave' or 'vacation leave', is paid holiday that all full-time employees receive for each year of employment they complete. Annual leave, which accrues after each completed year of service or employment, will be made available to all employees at the beginning of the year for use during the year in accordance with applicable leave rules and regulations of the organisation. While it is recognised that an employee who has continuous service of 12 months' or more is entitled to annual leave, such entitlement cannot be claimed as of right but is subject to the discretion of the employer. Therefore, an employee intending to take annual leave must apply and obtain prior permission from his employer before absenting himself from work.It is basically a matter of administrative discretion for the employer to grant or deny the request for annual leave.... in accordance with the provisions of the applicable rules and regulations of the organisation. The employer may deny annual leave requests for reasons that may be related to workload in the organisation. For example, the fact that some employees are granted annual leave during the period in question and that certain other employee or employees are required, due to unusual circumstances, to perfonn work during the period in question, among others. and until the annual leave request has been formally and properly approved by the company, an employee should not absent himself from work. Absenting